Employee Turnover Intensity Among Generation Z in Indonesia's Financing Industry - Muhammad Junaid Imansyah; Hangga Sev Aprilingga Eriawan; Adhitya Wibisono (The Indonesian Institute of Science and Technology Research, 2026)
The study aim is to examine and investigate the capacity of job satisfaction as a mediator in the relationship between factors such as career development, employee engagement, employee well-being, and work-life balance with the tendency of turnover intention to Generation Z employees at PT FIF. This research was conducted using an explanatory quantitative approach. Data were collected through questionnaires sent online to Generation Z employees. The respondents were determined using purposive sampling. To process and test the model, this study adopted the PLS-SEM statistical analysis method, supported by the Smart-PLS application, to analyze the relationships between the constructs. The data derived from the investigation show career development, employee welfare, and work-life balance positively and significantly influence job satisfaction. In contrast, the empirical analysis revealed that employee engagement does not exert a statistically significantly influence job satisfaction. Furthermore, the analysis revealed that these independent variables had no significant direct relationship with turnover intensity. Similarly, the job satisfaction as intermediary was not confirmed, and further research is needed to understand the causal nexus of job satisfaction and employee performance. The model has strong explanatory power for job satisfaction but is limited in explaining turnover intention. This study contributes to the literature by placing employee well-being as the dominant factor shaping the job satisfaction of Generation Z in the financing sector.